(untitled) (Web of Teachers: Inderscience Research, 2025)
This article is devoted to the coverage and significance of the educational games in the composition of the individual pedagogical technologies. The article in the article "Integration of educational process to the educational process in the educational process is to increase the interest of students, ensures the effectiveness of knowledge and serve to develop creative skills